Anayasa Mahkemesine Bireysel Başvuru Usulünde Başvuru Konusunun Nitelendirilmesi Meselesi. - ÖLMEZ, Cansu Bü!ra (Antalya Bilim University Law Review, 2026)
An individual application is a secondary and exceptional judicial remedy available to individuals who claim that a fundamental right guaranteed by the Constitution and the European Convention on Human Rights has been violated by public authorities, after exhausting ordinary legal remedies. Individuals exercising their right to individual application must, in principle, specify the fundamental rights and freedoms they claim have been violated in their application. However, applicants may sometimes find it difficult to present their allegations of violation on a legal basis. It is possible that the applicant may be unable to relate their complaint to a right or may misrepresent or inadequately describe the subject matter of the application. In such cases, the approach taken by the Constitutional Court when examining the application is crucial to the outcome of the application process. At this point, the principle of jura novit curia, which originates from Roman law and is expressed as 'the judge knows the law,' comes into play.